DARI IDE KE AGENDA PUBLIK: ANALISIS PRODUKSI KREATIF PROGRAM NEWS MAGAZINE SATU INDONESIA NET. - Rangga Permana; Shan Sujudi (Jurnal Kajian Budaya dan Humaniora, 2025)
Television as a mass medium plays a crucial role in shaping public perception through its audiovisual power, issue selection, and creative production strategies. In this context, NET.’s news magazine program Satu Indonesia serves as an intriguing case of how television combines the functions of information, entertainment, and public agenda-building through creative approaches. This study aims to analyze the development of creative ideas and production planning in Satu Indonesia, with a focus on the application of mass communication theory, journalism, news magazine format, agenda-setting, and television creativity. A descriptive qualitative method was employed, utilizing observation, interviews, and literature review, with data analysis conducted through Miles and Huberman’s interactive model. The findings reveal that Satu Indonesia employs narrative storytelling, aesthetic visualization, and multiplatform integration to present inspiring and timeless features. The program applies agenda-setting by prioritizing human interest and social solidarity issues, while framing reality from a positive perspective consistent with NET.’s identity as “Televisi Masa Kini.” Creativity emerges as the core of production, generated through collective collaboration among multitalented teams who balance journalistic professionalism with industry pressures. These findings affirm that modern television is not merely an information channel, but also a strategic site for the construction of social meaning.